Study of Fitness Cost in Three Rigid Ryegrass Populations Susceptible and Resistant to Acetyl-CoA Carboxylase Inhibiting Herbicides - Sabet Zangeneh, Hossein; Mohammaddust Chamanabad, Hamid R.; Zand, Eskandar; Asghari, Ali; Alamisaeid, Khalil; Travlos, Ilias S.; Alebrahim, Mohammad T. (Frontiers in Ecology and Evolution, 2016)
Evaluation of fitness differences between herbicide-resistant and susceptible weed biotypes, allows a better prediction of further dispersal of herbicide-resistance populations and the design of a management strategy in order to achieve a mitigation of the problem in the absence of herbicide. In this study an evaluation of germination and seedling emergence characteristics of three rigid ryegrass biotypes (one susceptible and two resistant populations with different mutations, namely Ile 1781 Leu and Ile 2041 Asn) and of competition between this weed and wheat using replacement series experiments was conducted. The results showed that when seeds were on the soil surface (0 cm) to depth of 2 cm and again for the depth of 6 cm, there were not any significant differences between the biotypes regarding seed germination percentage. On the contrary, when seeds were sown in 2-4 cm depth, R-1781 consistently displayed lower emergence than the S and R-2041 biotypes. Moreover, when seeds were sown at 8 cm depth, final proportions of emerged seedlings were similar for R-2041 and R-1781, while both populations had significantly higher emergence than the S population. The competitive ability of the three biotypes was similar, as determined by a replacement series experiment with wheat. Our results under competitive conditions revealed that Triticum aestivum was more competitive than Lolium rigidum. Overall, there was no apparent fitness penalty associated to ACCase-inhibitor resistance, while different mutations may impose different competitive ability and therefore require case-specific management strategies.